2022
DOI: 10.1038/s41467-022-29570-4
|View full text |Cite
|
Sign up to set email alerts
|

A polygenic risk score for nasopharyngeal carcinoma shows potential for risk stratification and personalized screening

Abstract: Polygenic risk scores (PRS) have the potential to identify individuals at risk of diseases, optimizing treatment, and predicting survival outcomes. Here, we construct and validate a genome-wide association study (GWAS) derived PRS for nasopharyngeal carcinoma (NPC), using a multi-center study of six populations (6 059 NPC cases and 7 582 controls), and evaluate its utility in a nested case-control study. We show that the PRS enables effective identification of NPC high-risk individuals (AUC = 0.65) and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“… 7 , 8 , 9 Of note, it has been suggested that PRS could also serve as a biomarker of disease outcomes, but the actual prognostic value of PRS in clinical practice has not been fully assessed. 10 , 11 , 12 Survival probability is a direct measure of cancer prognosis that is clinically important for patients suffering from cancer, 13 it, however, remains undetermined whether PRS can be utilized to predict cancer survival.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 9 Of note, it has been suggested that PRS could also serve as a biomarker of disease outcomes, but the actual prognostic value of PRS in clinical practice has not been fully assessed. 10 , 11 , 12 Survival probability is a direct measure of cancer prognosis that is clinically important for patients suffering from cancer, 13 it, however, remains undetermined whether PRS can be utilized to predict cancer survival.…”
Section: Introductionmentioning
confidence: 99%
“…A standard quality control protocol for genotypes was implemented in PLINK v1.9. The detailed information about genotyping and quality control was described in our previous study (He et al 2022 ). Individuals with call rate < 95%, gender discrepancy, extreme heterozygosity rate (inbreeding coefficient F > 6 SDs), or pairwise identify by descent (IBD) > 0.25 were removed from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As a group I carcinogen, EBV causes around 2% of all cancer cases worldwide every year, typically including NPC, EBV-associated lymphomas, and EBVaGC (Young and Dawson, 2014;Yin et al, 2019;He et al, 2022). Recent study has also identified that long-term EBV infection results in chronic inflammatory demyelinating disease of the central nervous system, such as multiple sclerosis (Bjornevik et al, 2022;Bordon, 2022;Robinson and Steinman, 2022;Sollid, 2022).…”
Section: Ebv Infection In Tumorigenesismentioning
confidence: 99%